The epidemiology of chronic venous insufficiency in Portugal. - Capitão, L M; Menezes, J D; Gouveia-Oliveira, A (Acta Médica Portuguesa, 1995)
The prevalence of chronic venous insufficiency (CVI) was investigated in 44,777 unselected primary care outpatient clinics in 17 of the 20 districts in Portugal, during 1993. The diagnosis of CVI was established clinically by 427 participating general practitioners. CVI was more prevalent in females, with a female to male ratio of 2.1:1. The disease affects all age groups, but in females its prevalence increases sharply between 15 and 20 years, while in males it begins to become important about 10 years later. The maximum age-specific prevalence is reached between 55 and 64 years in both sexes, when CVI is present in 58% of females and in 35% of males. Overall prevalence of CVI was calculated using the data from the population census of 1991, by the direct standardization method. The estimated prevalence of CVI in males is 17.8% and in females is 34.1%, corresponding to 812 thousand and 1,741 thousand cases in Portugal, respectively. In the population over 15 years old, the prevalence is 20.7% in males and 40.8% in females. These estimates have an error of +/- 2.5% with 95% confidence. The geographical distribution of the disease showed different patterns in males and in females. Prevalence decreases from coast to inland in males, and from south to north in females.